Strategi Marketing Mix Berbasis Syariah Untuk Meningkatan Kinerja Penjualan Toko May Collection Probolinggo - Latifah, Al Mar'atul; Al Mar'atul; Meilinda, Fauziyah Putri (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2026)
The increasingly competitive business environment requires MSMEs (Micro, Small, and Medium Enterprises) to implement marketing strategies that are not only economically effective but also aligned with Sharia values. May Collection Probolinggo, a Muslim fashion business, faces challenges in improving sales performance amidst business location constraints and limited consumer purchasing power. This study aims to analyze the Sharia-based marketing mix strategy in increasing the sales turnover of May Collection Probolinggo. The research employs a descriptive qualitative method with a field research approach. The qualitative method was selected to gain a profound understanding of marketing practices, the implementation process of the marketing mix, and the internalization of Sharia values in business activities that cannot be measured quantitatively. The field research approach was utilized to obtain primary data directly from the field within authentic social and economic contexts. Data collection was conducted through observation, in-depth interviews, and documentation. Respondents were selected using a purposive sampling technique, featuring the owner of May Collection as the key informant and repeat customers as supporting informants. The results indicate that the implementation of the marketing mix elements product, price, place, and promotion has been executed in an integrated manner with Sharia marketing principles, which include theistic, ethical, realistic, and humanistic values. This strategy has proven capable of improving sales performance while strengthening consumer trust and loyalty. This study concludes that a Sharia-based marketing mix is an effective and sustainable strategy for the development of MSMEs.